2021
DOI: 10.3390/ijms22041947
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Targeting Ligand ST-2223 with Histamine H3 Receptor and Dopamine D2/D3 Receptor Antagonist Properties Mitigates Autism-Like Repetitive Behaviors and Brain Oxidative Stress in Mice

Abstract: Autism spectrum disorder (ASD) is a complex heterogeneous neurodevelopmental disorder characterized by social and communicative impairments, as well as repetitive and restricted behaviors (RRBs). With the limited effectiveness of current pharmacotherapies in treating repetitive behaviors, the present study determined the effects of acute systemic treatment of the novel multi-targeting ligand ST-2223, with incorporated histamine H3 receptor (H3R) and dopamine D2/D3 receptor affinity properties, on ASD-related R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 105 publications
(152 reference statements)
1
18
0
Order By: Relevance
“…Contrary, CUR (25, 50, and 100 mg/kg) were capable of restoring the levels of CAT levels in the cerebellum, but failed to alter the levels of SOD in the hippocampus. The results observed on the levels of oxidative stress markers are in harmony with numerous previous preclinical reports from our group and other research groups that investigated the effects of synthetic ligands modulating brain ACh levels on oxidative stress in the brains of different rodent models [53][54][55][56][57]. Also, the results observed for CUR are in harmony with a previous preclinical study in which CUR was found to mitigate the disturbed levels of IFN-γ, serotonin, glutamine, reduced glutathione, glutathione S-transferase, lipid peroxidase with an increase in CYP450, IL-6, glutamate, and oxidized glutathione in valproate-induced ASD in rats [58].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Contrary, CUR (25, 50, and 100 mg/kg) were capable of restoring the levels of CAT levels in the cerebellum, but failed to alter the levels of SOD in the hippocampus. The results observed on the levels of oxidative stress markers are in harmony with numerous previous preclinical reports from our group and other research groups that investigated the effects of synthetic ligands modulating brain ACh levels on oxidative stress in the brains of different rodent models [53][54][55][56][57]. Also, the results observed for CUR are in harmony with a previous preclinical study in which CUR was found to mitigate the disturbed levels of IFN-γ, serotonin, glutamine, reduced glutathione, glutathione S-transferase, lipid peroxidase with an increase in CYP450, IL-6, glutamate, and oxidized glutathione in valproate-induced ASD in rats [58].…”
Section: Discussionsupporting
confidence: 90%
“…injections of MLA (1 µg/kg). Doses of CUR, DOZ, and MLA were selected according to previous experimental protocols C57 mice as well as BTBR mice [ 10 , 38 , 48 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. In these studies, a dose range of 15–125 mg/kg was used to assess several in vivo effects of CUR in mice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations